Targeting a membrane-proximal epitope on mesothelin increases the tumoricidal activity of a bispecific antibody blocking CD47 on mesothelin-positive tumors. Issue 1 (1st January 2020) - Hatterer, Eric; Chauchet, Xavier; Richard, Françoise; Barba, Leticia; Moine, Valéry; Chatel, Laurence; Broyer, Lucile; Pontini, Guillemette; Bautzova, Tereza; Juan, Flora; Calloud, Sebastien; Bosson, Nicolas; et al.
ABSTRACT: Mesothelin (MSLN) is a cell surface glycoprotein overexpressed in several solid malignancies, including gastric, lung, mesothelioma, pancreatic and ovarian cancers. While several MSLN-targeting therapeutic approaches are in development, only limited efficacy has been achieved in patients. A potential shortcoming of several described antibody-based approaches is that they target the membrane distal region of MSLN and, additionally, are known to be handicapped by the high levels of circulating soluble MSLN in patients. We show here, using monoclonal antibodies (mAbs) targeting different MSLN-spanning epitopes, that the membrane-proximal region resulted in more efficient killing of MSLN-positive tumor cells in antibody-dependent cell-mediated cytotoxicity (ADCC) assays. Surprisingly, no augmented killing was observed in antibody-dependent cellular phagocytosis (ADCP) by mAbs targeting this membrane-proximal region. To further increase the ADCP potential, we, therefore, generated bispecific antibodies (bsAbs) coupling a high-affinity MSLN binding arm to a blocking CD47 arm. Here, targeting the membrane-proximal domain of MSLN demonstrated enhanced ADCP activity compared to membrane-distal domains when the bsAbs were used in in vitro phagocytosis killing assays. Importantly, the superior anti-tumor activity was also translated in xenograft tumor models. Furthermore, we show that the bsAb approach targeting the membrane-proximal epitope of MSLN optimized ADCC activity by augmenting FcγR-IIIA activation and enhanced ADCP via a more efficient blockade of the CD47/SIRPα axis.